KONSEP PENGELOLAAN ZAKAT UNTUK PALESTINA DALAM PRESPEKTIF MAQSHID SYARIAH - HAKIM, RIDWAN; SYAUQI BEIK, IRFAN; IBDALSYAH, IBDALSYAH (Universitas Ibn Khaldun Bogor, 2023)
The widespread organization of zakat and Islamic philanthropy for Palestine is gaining media attention rapidly, driven by the shared Islamic beliefs and historical relations with Indonesia dating back to the early days of independence. The community and government are united in supporting the Palestinian cause through Islamic philanthropy, emphasizing the importance of guidelines to ensure funds are utilized effectively. Maqashid sharia, a legal instrument in Islam, is deemed suitable for this purpose. This qualitative research uses normative legal methods to establish guidelines for zakat management and Islamic philanthropy for Palestine from a maqashid sharia perspective. The study recommends that zakat be allocated for dharuriyat and hajjiyat programs in Palestine, with other Islamic philanthropy supporting tahsiniyat. Philanthropic associations for Palestine should prioritize educating donors on intentions and ethical practices. The Islamic philanthropic programs for Palestine should focus on safeguarding religion, life, mind, property, and descendants, with targets including protecting al-Aqsa and Islamic symbols, fulfilling the human rights of Palestinians, and supporting independence efforts led by both nations' leadership.